2014
DOI: 10.1016/j.actamat.2014.06.014
|View full text |Cite
|
Sign up to set email alerts
|

A mesoscale solidification simulation of fusion welding in aluminum–magnesium–silicon alloys

Abstract: A 3-D granular model has been developed to simulate solidification during fusion welding of Al alloys. The model simulates the gradual development of the weld mushy zone composed of both continuous liquid films and solidifying grains by coupling thermal fields based on the Rosenthal equation, a modified Voronoi tessellation to provide grain structure at the mesoscale, and the evolution of solid fraction within a grain based on the Scheil equation. The shape and geometry of the columnar and equiaxed grains with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Control is generally achieved by adjustment of the wire composition and tentative to form an equiaxed zone. Studies have been reported to model the grain structure developed in welding processing together with prediction of the internal pressure [2] or the liquid feeding ability at intergranular liquid channels [3]. The mechanical properties of the joints are also linked to the anisotropy of the grain structure developed in the weld bead, especially in case of multiples passes processes when large grains develop [4].…”
Section: Introductionmentioning
confidence: 99%
“…Control is generally achieved by adjustment of the wire composition and tentative to form an equiaxed zone. Studies have been reported to model the grain structure developed in welding processing together with prediction of the internal pressure [2] or the liquid feeding ability at intergranular liquid channels [3]. The mechanical properties of the joints are also linked to the anisotropy of the grain structure developed in the weld bead, especially in case of multiples passes processes when large grains develop [4].…”
Section: Introductionmentioning
confidence: 99%
“…The semisolid region of a weld, called the mushy zone, consists of grains forming a solid body within a network of micro liquid channels covering each grain [1][2][3]. At high solid fraction, the micro liquid channels may deform due to the solidification shrinkage, if a lack of feeding is present, and consequently induce local tensile deformation [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The width and thickness of the base metal are assumed to be 50 mm and 3 mm, and the simulated weld length is set at 20 mm. The shape of the material removed representing the weld pool is given by the welding procedure, and was determined experimentally [18]. As shown in Fig.…”
Section: Geometry (And Boundary Conditions) Modulementioning
confidence: 99%
“…The Solidification module uses the model of Zareie Rajani et al [18] to simulate solidification of the weld pool at the meso-scale. This model is composed of both columnar and equiaxed solid grains and also a network of micro liquid channels spread between each grain; the fully solid microstructure is generated from a series of Voronoi tessellations performed on different regions in space.…”
Section: Meso-scale Solidification Modelmentioning
confidence: 99%
See 1 more Smart Citation